Islamic Law and Gender: The Collapse of the Oligarchical-Patriarchal Culture in the Konawe Region of Southeast Sulawesi - Ipandang Ipandang (Islam Realitas: Journal of Islamic and Social Studies, 2020)
This article focuses on the efforts of women in the Konawe Region of Southeast Sulawesi who seek to gain an egalitarian position in the midst of oligarchical-patriarchal culture. Divorce claims as a trend of regional social become the main discourse on the dynamics of marriage law – in this context of Islamic law perspective. It is ordinarily for this research to use a qualitative approach aimed at forming substantive theories based on the concept of empirical data. The informants of this article were determined using a purposive technique, data collection techniques using in-depth interviews and participant observation, and the interactive model of Miles and Hubermann was used as a data analysis model. This research conclusively found that the power of oligarchic-patriarchal culture lies and legitimized by the interpretation of Islamic religious texts from the Qur’an and Sunnah. This effort also appears massive in the form of "rebellious" actions such as divorce to form an asymmetrical culture. This research examined this pattern in terms of asymmetric gender, namely the movement egalitarian of women who are incompatible with the ideals of male superiority in patriarchal-culture religion.Artikel ini fokus pada upaya perempuan masyarakat Daerah Konawe Sulawesi Tenggara yang berusaha mendapatkan posisi egaliter di tengah budaya oligarkis-patriarkis. Gugat cerai sebagai tren kemasyarakatan daerah tersebut menjadi diskursus utama dinamika hukum pernikahan –dalam konteks ini perspektif hukum Islam. Lazim apabila riset ini menggunakan pendekatan kualitatif yang ditujukan pada pembentukan teori substantif berdasarkan konsep data empiris. Informan artikel ini ditentukan dengan teknik purposive, teknik pengumpulkan data menggunakan wawancara mendalam dan observasi partisipan, dan model interaktif Miles dan Hubermann dijadikan sebagai model analisis data. Riset ini secara konklutif menemukan, keperkasaan budaya oligarkis-patriarkis ada serta dilegitimasi oleh penafsiran terhadap teks-teks keagamaan Islam dari Qur’an dan Sunnah. Upaya ini pun masif muncul dalam bentuk tindakan “memberontak” seperti gugat cerai hingga membentuk budaya asimetris. Riset ini mengistilahkan pola tersebut dengan istilah gender asimetris, yaitu gerakan egaliter kaum perempuan yang tidak kesesuaian dengan cita superioritas laki-laki di budaya patriarkis-religius